Chemical Profiling Combined with "Omics" Technologies (CP‐Omics): a Strategy to Understand the Compatibility Mechanisms and Simplify Herb Formulas in Traditional Chinese Medicines. Issue 5 (7th April 2017) - Xu, Tengfei; Pi, Zifeng; Liu, Shu; Song, Fengrui; Liu, Zhiqiang
Abstract: Introduction: The compatibility mechanisms of formulas in traditional Chinese medicine (TCM) are indistinct. In order to better understand the compatibility mechanisms and the quality control of the formulas, it is necessary to simplify formulas in TCM research. Objective: Developing a novel method by multi‐analysing the contents of different compounds in formula and inferred simplified formula simultaneously. Methodology: Chemical profiling combined with "omics" technologies (CP‐omics) was employed in the present study. Wu‐tou Tang (WTT) was taken as an example to elucidate the workflow. We used high definition mass spectrometry combined with pattern recognition methods to analyse WTT and eight herb combinations derived from it. By analysing the content variation of the compounds, the inter compatibility mechanisms of WTT was explained. Cluster analysis classified the herb combinations and inferred a simplified formula. Results: It was found that Glycyrrhiza Radix Preparata and Ephedrae Herba could reduce the contents of diester‐diterpenoid alkaloids; Ephedrae Herba could increase the contents of triterpene saponins and monoterpene glycosides in WTT. Through the overall comparison, Aconiti Radix Preparata combined with Glycyrrhiza Radix Preparata, Ephedrae Herba combined with Glycyrrhiza Radix Preparata have a similar chemical profiling with WTT. We inferred that a new simplified prescription composed of Aconiti Radix Preparata, Ephedrae Herba and Glycyrrhiza Radix Preparata should also have a good clinical effect. At last, pharmacological results confirmed that the new herb combination possesses similar anti‐inflammatory activities to WTT. Conclusion: Our results demonstrated that the CP‐omics has great advantages in pharmaceutical discovery and optimising complex formulas in TCM. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A novel herb formula discovery strategy in traditional Chinese medicine (TCM) based on chemical profiling combined with "omics" technologies (CP‐omics) was developed. CP‐omics could multi‐analyse the contents of great many compounds simultaneously. CP‐omics method contributes to understand the inter mechanisms of formula. CP‐omics possesses advantages in simplify complex formulas. Pharmacological results verified the rationality of the new herb combination.